Transcriptome Analysis of Sugarcane Response to Sugarcane Yellow Leaf Virus Infection Transmitted by the Vector Melanaphis sacchari - Shabbir, Rubab; Zhaoli, Lin; Yueyu, Xu; Zihao, Sun; Pinghua, Chen (Frontiers in Plant Science, 2022)
Sugarcane yellow leaf disease severely affects sugarcane production. As a viral disease, the pathogen sugarcane yellow leaf virus can only be transmitted by aphid vectors rather than mechanical means. To understand the sugarcane responses to ScYLV infection, the corresponding transcriptomic profile of ScYLV infected and ScYLV free plants were analyzed with the RNA-seq technology. In this study, Melanaphis sacchari was used as the vector to transmit ScYLV to the susceptible sugarcane cultivar CP72-1210 and transcriptome was sequenced as well as differentially expressed genes between disease infected and non-infected sugarcane plants were investigated. A total of 122593 genes were assembled, of which 1630 genes were differentially expressed. Among DEGs, 1622 were up-regulated and 8 were down-regulated that were further annotated with GO, KEGG, KOG, PFAM, Swissprot, and Nr databases. The expression levels of DEGs in the three KEGG pathways, namely endocytosis, PEX protein synthesis, and endoplasmic reticulum stress response to viral protein synthesis were observed. Interestingly, it was found that yellow leaf virus could induce the formation of autophagosomes by LC3, promoted by ER stress, and may be related to the replication of viral RNA. We tested 63 DEGs in this research. The qRT-PCR results showed that 2 were down-regulated and 45 were up-regulated in response to ScYLV infection. The current study will not only offer an overall comprehension of sugarcane responses to ScYLV infection at the gene expression level but also increases the chances to block up the transmission of ScYLV for the use in further molecular biology techniques and will aid in increasing the resistance of plants against ScYLV.